HUBUNGAN CULTURE SHOCK DENGAN TINGKAT STRESS PADA SANTRI BARU DI PONDOK AL-AMIN PRENDUAN - Syamsul Arifin; Eko Mulyadi; Sugesti Alitifah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
ABSTRACT Social phenomena that often occur in students in Islamic boarding schools are culture shock or cultural unfamiliarity in the cottage with life before being in the cottage. Culture shock causes stress in Islamic boarding schools, especially for new students who are still in the stage of adaptation. The purpose of this study is to analyze the relationship between culture shock and stress levels in new students at Pondok Al-Amin Prenduan. This type of research is cross sectional, independent variable is culture shock and stress dependent variable. One month research time at Al-Amin Islamic Boarding School, population 94 people, sample 76 people, sampling technique using simple random sampling. Research instruments using questionnaires.The results showed that most respondents experienced culture shock. Half the respondents experienced moderate stress. There is a relationship between culture shock and stress level in new students at Pondok Al-Amin Prenduan. Nurses conduct collaborative interventions with the Al-Amien Islamic Boarding School to provide education about mental health while in the cottage. Education also involves Husada santri as a health cadre in the pondok environment to create a conducive social environment so that it becomes social coopening to maintain the mental health of santri. Keywords: Santri, culture shock, stress ABSTRAK Fenomena sosial yang sering terjadi pada santri di pondok pesantren adalah culture shock atau ketidakbiasaan budaya di pondok dengan kehidupan sebelum di pondok.Culture shockpenyebab stress di pondok pesantren terutama bagi santri baru yang masih dalam tahap adaptasi. Tujuan penelitian menganalisis hubungan culture shock dengan tingkat stress pada santri baru di Pondok Al-Amin Prenduan. Jenis penelitian cross sectional, Variabel independen culture shockdan variabel dependen stress. Waktu penelitian satu bulan di Pondok Pesantren Al-Amin Populasi 94 orang,sampel 76 orang, teknik sampling menggunakan simple random sampling. Instrumen penelitian menggunakan kuisioner. Hasil penelitian menunjukkan sebagian besar responden mengalami culture shock.Setengah respondenmengalami stres sedang. Ada hubungan culture shock dengan tingkat stress pada santri baru di Pondok Al-Amin Prenduan. Perawat melakukan intervensi kolaboratif dengan Pondok Pesantren Al-Amien untuk memberikan edukasi tentang kesehatan mental selama di pondok. Edukasi juga melibatkan santri husada sebagai kader kesehatan di lingkungan pondok untuk menciptakan lingkungan sosial yang kondusif sehingga menjadi kooping sosial untuk mempertahankan kesehatan mental santri. Kata kunci : Santri, culture shock, stress